The role of high-performance work practices and affective commitment in promoting knowledge sharing behavior in higher education institutions (Global Business Management Review (GBMR), 2024)
Although high-performance work practices (HPWPs) are well-known for promoting desired attitudes and behaviors among organizational members, the current literature has overlooked measuring the impact of HPWPs on knowledge sharing behavior (KSB) in the academic setting. Thus, considering the research gap and the pivotal role of knowledge sharing practices in academic institutions, this study aims to explore the aforesaid relationship in the realm of higher education institutions (HEIs) from the perspective of social exchange theory. Moreover, the study aims to explore affective commitment (AC) as a connector between HPWPs and KSB. The study amassed data conveniently using a structured questionnaire from 255 private university teachers serving in Bangladesh. The sample size was relatively small owing to limited access and the considerable time constraints of the respondents. The outcomes of SEM-PLS analysis revealed five HPWPs (i.e., selective staffing, training, performance appraisal, compensation, and participation) as successful predictors of both AC and KSB. Moreover, AC mediated the link between these five HPWPs and KSB, meaning that AC plays an important role in explaining how HPWPs influence KSB. However, clear job description did not significantly predict KSB either directly or indirectly through AC. This study introduces fresh insights into the concept of high-performance work system showing how its individual practices shape the willingness of academics to share knowledge directly and via AC. The study’s findings imply that HEIs should incorporate HPWPs (e.g., attractive compensation, participative decision-making) into their people management systems to enhance faculty members’ organizational commitment and knowledge sharing practices, thereby achieving long-term success and sustainability.